FEATURES OF EXPERIMENTAL INSTALLATION FOR PRODUCING FUNCTIONAL FOOD MONO PRODUCTS - Shegelman I. R., Shchukin P. O., Sukhanov I. V. (A breakthrough in science: development strategies, 2019)
the experimental setup was created on the basis of the technical specifications, outline design documentation and established project requirements
Keywords: эксперименты; experiments; функциональные пищевые продукты; functional foods; монопродукты; monoproducts